MAKNA DAN FUNGSI MANTRA PENGOBATAN DALAM MASYARAKAT MELAYU BELITANG - Kadarsih, Nunung; Priyadi, Totok; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractOral literature is one of literary work made and recited orally as a part of art performances as well as in ordinary occasion. It tells about occurring events or the culture of a society. The general problems in this research was the environment of the recited spells, the meaning of the spells, and the function of the spells as an oral literature. Theories and studies used in this research were oral literature in features, forms and functions, environment of recited spells, heuristical and heumaristical reading, functions of spells, interpreting theory, semiotical structures, study planning in schools, and literature study. This was a descriptive method research in form of qualitative study with semiotical approach. The main source of this research was the reciter of the spell, and the data were the recited spells in form of words.The analysis results of the healing spells of Melayu Belitang people found that there were twenty environments of recited spells, twenty spells meanings of three religious interpretation, self trait meaning, and society meaning. It also discovered that there were fourteen functions of healing spells such as belief, social, cultural, educational, communication, and the literary function itself. Hopefully, the suggestions of this research can be beneficial for future research and learning material in schools.Â Keywords: meaning, function, healin spells. Â